Efeitos da terapia fotodinâmica mediada por um novo dispositivo de luz comparada a compostos químicos indicados para descontaminação da resina acrílica - Prado, Janaina Câncio de Holanda (2015)
Disinfection or sterilization of acrylic resin devices, such as immediate prostheses, surgical guides and gutters, is important in preventing the patient from contamination by potentially pathogenic microorganisms. Acrylic resins are heat-sensitive materials, which can only be decontaminated by chemicals or cold means. This study aimed at making a systematic review of literature on the antimicrobial action of chemical agents on acrylic resins. In addition, it was carried out an experimental study evaluating the effect of photodynamic therapy, mediated by methylene blue photosensitizer to 22 μM, on the level of contamination by microorganisms present in dentures coming from different laboratories, and a new device consisting of light emitting diodes (LEDs) 630 nm and 1W. For the literature review, we used the descriptors microorganisms, dental prosthesis, and/or disinfection in Pubmed/ Bireme databases with search from 2004 to 2014, including articles in English on experimental studies comparing chemical agents on more than one species of microorganism in the surface of acrylic resin. It was found that methods show differences in antimicrobial effects depending on the immersion time, product concentration and type of present microorganism. Sodium hypochlorite 1%, chlorhexidine digluconate 2% and acetic acid showed greater efficacy, in decreasing order. In the experimental study, a number of 25 upper dentures were selected and installed in patients. Then, the dentures were randomly distributed into four groups: untreated; immersion in 2% chlorhexidine digluconate for 10 minutes; only irradiation with LEDs; photodynamic therapy (PDT). The control circuit and activation of equipment consisting of 8 LEDs 1W was developed in partnership with the Computer System Engineering Laboratory at the Faculty of Computer Engineering at the Federal University of Ceará. On the PDT group, irradiation for 1 minute took place 5 minutes after application of the photosensitizer. After the treatment, the prostheses were immersed in 100 ml of BHI broth and then brought to ultrasonic tank for 15 minutes. It was collected 5 ml of this culture for incubation for 48 hours at 37 ° C. After that, 1000 microliter of the broth were diluted 1:10, 1: 100, 1: 1000 and plated in triplicate, on Blood Agar, Sabouraud Dextrose Agar and HiCrome UTI Ágar®. The plates were incubated at 37°C for 48 h and then counting colony forming units (CFU / ml) and classification of data on an ordinal scale. Kruskal-Wallis test, Dunn, ANOVA (2 criteria) and Bonferroni (α = 0.05) were applied. PDT showed significant reduction in count of total viable bacteria (p = 0.0002) compared to only irradiated group, and a significant reduction of total viable fungi, when compared to the only irradiated groups and untreated (p = 0.0002). PDT showed antimicrobial effect similar to immersion in 2% chlorhexidine digluconate for 10 minutes (p> 0.05). The most prevalent bacterial species identified in the prostheses were P. aeruginosa, K. pneumoniae and E. coli and PDT caused a significant decrease in counting of these species as well as chlorhexidine did (p <0.001). The contamination of dental prostheses coming from prosthetic laboratories was significant. Photodynamic therapy used in the proposed protocol for acrylic resin devices showed promising antimicrobial effect by this contamination.